Identifying Student Speaking Anxiety at English Language Education Universitas Internasional Batam - Pipit Rahayu; Eripuddin Eripuddin; Annisa Salsabila; Nantakarn Tohmi; Pawinee Suksawai (INTERNATIONAL JOURNAL OF LANGUAGE PEDAGOGY, 2022)
There are four focus in pursuing language, which is Speaking, Writing, Listening and Reading. The Speaking skill commonly used as a sole way to interact and communicate with another individual in daily basis or even in more formal basis like academic or even business. But still students still tend to have anxiety when speaking in another language because of several causes and reason. Therefore, this research aims to identify what is the cause and type of the problems of anxiety at English Language Education (ELE) students Universitas Internasional Batam. This study conducted qualitative method for the research. The research instruments were questionnaires. To extend the deeper analysis, this study also conducted an in-dept interview adopted from SLSAS Woodrow (2006) and FLCAS by Horwitz et al. (1986). From the result the researcher can define the types and causes of the ELE students speaking anxiety at Universitas Internasional Batam. Therefore, the learning process at English Language Education needs to be equipped with sufficient linguistic competences, such as grammar, pronunciation, and vocabulary.